Partial purification of trypsin inhibitors from Parkia seeds (Fabaceae) - Larissa Ramos Chevreuil; José Francisco de Carvalho Gonçalves; Leonardo de Azevedo Calderon; Luiz Augusto Gomes de Souza; Silvana Cristina Pando; Eduardo Euclydes de Lima e Borges (Hoehnea)
Leguminous seeds (Fabaceae) have a high content of inhibitors of which serine protease inhibitors are the most widely studied. However, there are only a few studies related to the investigation of these proteins in tree species belonging to the Amazon flora. The protein content presented in seeds of four Amazonian Leguminosae species, Parkia pendula, P. discolor, P. multijuga and P. Nitida, was extracted by using NaCl 0.15 mol L-1 and then partially fractionated by using affinity chromatography performed on a trypsin-Sepharose 4B. These inhibitors presented different affinities between trypsin and chymotrypsin serine proteases, showing a higher inhibition to trypsin compared to chymotrypsin, except for P. nitida, which showed high inhibition against both enzymes. The SDS-PAGE analysis showed that the species from Parkia genus have a main band corresponding to partially purified trypsin inhibitors. The apparent molecular mass inhibitors (approximately 13-18 kDa) and the high specificity for trypsin suggest the occurrence of Bowman-Birk and Kunitz type inhibitors.